Mathematics

Question

-3b-(-2)=4b-12 show work please ASAP

2 Answer


  • Solve the equation:

    – 3b – (– 2) = 4b – 12

    – 3b + 2 = 4b – 12

    – 3b = 4b – 12 – 2

    – 3b = 4b – 14

    – 3b – 4b = – 14

    – 7b = – 14

            – 14
    b = ———
             – 7


    b = 2   <———   solution.


    I hope this helps. =)

  • -3(b) - (-2) - (4(b)) which is equal the number 0 
    -7(b) + 14
    Now, lets solve → -7 = 0 
    b - 2 = 0 
    Next, we add the number 2 to each of the sides of your problem 
    Therefore, the result of b is 2 

NEWS TODAY